A educação física escolar e sua representação para a comunidade LGBTQIAPN+: experiências, desafios e expectativas de egressos do ensino médio - Caetano, Fagner Roberto (2025)
Brazil has been going through a period of uncertainty and setbacks in the rights and achievements of the LGBTQIAPN+ community. This situation is characterized by inequality in gender perspectives and political clashes that often reinforce conservative discourses, hindering progress in ensuring sexual diversity. However, it is important to emphasize that, despite these setbacks, there is ongoing resistance in defense of the rights of this community. In the school context, where inclusion should be a fundamental principle, acts of discrimination, intolerance, and prejudice continue to persist, creating a hostile environment for this community. This study aimed to investigate the perceptions of LGBTQIAPN+ students regarding Physical Education in schools. The participants had recently completed high school in a municipality in the interior of São Paulo. The research sought to understand their experiences, challenges, and expectations. To this end, semi-structured interviews were conducted with seven graduates from a public school in the municipal education network of Matão-SP. The interviews, consisting of thirty-three questions, included participants with diverse sexual orientations and gender identities. The data were analyzed using the Situated Phenomenon Analysis approach. The results identified three main categories. The first revealed that the dominance of traditional sports in Physical Education contributes to the exclusion of LGBTQIAPN+ students, reinforcing gender stereotypes and limiting the diversity of sports practices. The predominance of traditionally male-oriented activities and the gender-segregated organization of classes lead to marginalization, insecurity, and fear of judgment, making the environment exclusionary. This highlights the need to revise pedagogical practices and promote diversity to create a safer and more equitable space. The second category demonstrated that open dialogue between teachers and peers can help reduce prejudice and foster a more welcoming environment. However, significant challenges remain, such as the lack of teacher training, the absence of formal discussions on diversity, and the need for structural changes in pedagogical practices. These factors underscore the urgency of concrete actions to ensure a more just and inclusive school environment. Finally, the third category highlighted that, despite some progress—such as the presence of more inclusive teachers—change remains slow. Barriers such as prejudice, cultural resistance, and the lack of institutional support hinder inclusion. Additionally, LGBTQIAPN+ students' participation in Physical Education classes often depends on athletic performance, further limiting their full inclusion. To overcome these barriers, participants suggested diversifying activities, promoting teacher discussions, and implementing awareness-raising initiatives. Achieving effective inclusion requires not only pedagogical adaptations but also a cultural shift in the school environment, ensuring that all students feel valued and respected. The study revealed that, despite advances, heteronormative norms continue to hinder inclusion, emphasizing the need for teacher training, the deconstruction of stereotypes, and more inclusive pedagogical strategies. We reaffirm the importance of rethinking Physical Education as an inclusive space, grounded in practices that recognize and respect gender and sexual diversity.